Psychological Analysis of Jokowi’s First 100 Days and Nawacita from Text in Twitter - Indro Adinugroho; Smitha Sjahputri; Judotens Budiarto; Roby Muhamad (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2018)
In recent days, the public often uses social media such as Twitter for delivering critics; appreciation and campaign related to Government and political issues. The existence of Twitter is changing human behavior rapidly. This study aims to identify Twitter as a medium to generate public opinion concerning two political issues, the 7th Indonesian President first 100 days and public response towards his strategic plan, Nawacita. Method applied in this study is a combination of contemporary research instruments that combines technology and psychology. In this study, the authors examined conversation on Twitter by using Tracker and Algoritma Kata (AK, words algorithm). Tracker is used to collecting conversation on twitter regarding Jokowi’s first 100 days and Nawacita, whereas AK is applied to identify valence and arousal in each tweet collected by Tracker. The finding shows the domination of positive tweets in every week. However, there is a moment where the number of positive tweets was close to negative tweets. In Nawacita issue, law reformation and enforcement was the issue that has highest negative sentiment among others.